Description of the tree stratum in combination with rustic coffee in a medium subperennifolia rainforest, Jocotepec, Oaxaca - Moreno-Guerrero, Víctor; Ortega-Baranda, Verónica; Sánchez-Bernal, Edgar Iván; Nieto-Castañeda, Irma Gisela (REVISTA TERRA LATINOAMERICANA, 2020)
Agroforestry systems (SAF) of coffee are considered areas that increase the biodiversity of species of both flora and fauna, are sources of economic income for the communities that work them, as well as multiple environmental services. In order to know the influence of coffee SAF management on the diversity of tree species, the composition, structure and diversity of the tree stratum in two rustica coffee plantations was described, under management conditions: active coffee (CA) and abandoned coffee plantation (CAb), in Jocotepec, region Coast of Oaxaca. In each driving condition four study units of 20 × 30 m (0.06 ha) were placed. All trees individuals from 1.30 m above the ground were registered with the normal diameter (DN) ≥ 2.5 cm, total height and canopy cover. Wealth, vertical, horizontal structure, Importance and Forest Value Indices (IVI and IVF) were evaluated; diversity with the Simpson Indices modified by Pielou (1-D) and Shannon-Weaver (H´) and equity (E), dominance (D) and Similarity. A wealth of 35 species was obtained for the CA and 31 in CAb; The main taxonomic families were Fabaceae, Lauraceae and Moraceae. In both driving conditions, the diameter category 5 (2.5 - 7.5 cm) exceeded the number of tree individuals, with a distribution of heights that revealed the existence of two vertical strata. The species that presented a high IVI and IVF in CA were: Cedrela odorata, Tabebuia rosea and Quercus crispifolia and for the CAb: Quercus sp., Ficus tecolutensis and Ocotea helicterifolia. Between CA and CAb there were no differences in the evaluated variables, 1-D, H´, E and D. The floristic similarity between conditions was 52%.